Dietary Fiber Pectin Ameliorates Experimental Colitis in a Neutral Sugar Side Chain-Dependent Manner - Ishisono, Keita; Mano, Toshiyuki; Yabe, Tomio; Kitaguchi, Kohji (Frontiers in Immunology, 2019)
Dietary fiber, with intake of soluble fibers in particular, has been reported to lower the risk for developing inflammatory bowel diseases (IBD). This is at least partly attributable to the fermentation of dietary fiber by the colonic microbiota to produce short chain fatty acids. Pectin, a widely consumed soluble fiber, is known to exert a protective effect in murine models of IBD, but the underlying mechanism remains elusive. Apart from having a prebiotic effect, it has been suggested that pectin direct influences host cells by modulating the inflammatory response in a manner dependent on its neutral sugar side chains. Here we examined the effect of the side chain content of pectin on the pathogenesis of experimental colitis in mice. Male C57BL/6 mice were fed a pectin-free diet, or a diet supplemented with characteristically high (5% orange pectin) or low (5% citrus pectin) side chain content for 10–14 days, and then administered 2,4,6-trinitrobenzene sulfonic acid or dextran sulfate sodium to induce colitis. We found that the clinical symptoms and tissue damage in the colon were ameliorated in mice that were pre-fed with orange pectin, but not in those pre-fed with citrus pectin. Although the population of CD4+Foxp+ regulatory T cells and CD4+RORγt+ inflammatory T cells in the colon were comparable between citrus and orange pectin-fed mice, colonic interleukin (IL)-1β and IL-6 levels in orange pectin-fed mice were significantly decreased. The fecal concentration of propionic acid in orange pectin-fed mice was slightly but significantly higher than that in control and citrus pectin-fed mice. However, the protective effect of orange pectin against colitis was observed even in mice treated with antibiotics. IL-6 production from RAW264.7 cells stimulated with the toll-like receptor agonist Pam3CSK4 or lipopolysaccharide was suppressed by pre-treatment with orange pectin in vitro. Taken together, these results suggest that the side chains of pectin not only augment prebiotic effects but also directly regulate IL-6 production from intestinal macrophages in a microbiota-independent fashion to attenuate colitis.